Coativação linguística bimodal: um estudo sobre reconhecimento visual de palavras por estudantes surdos - Patrícia Rodrigues de Souza (2025)
In recent years, research in Psycholinguistics of Bilingualism has shown evidence of linguistic coactivation in bimodal bilinguals, deaf and hearing, especially adults (Morford et al., 2011, 2014). The objective of this research is to investigate how lexical access occurs in deaf bilingual students of the Libras-Portuguese pair, observing whether both languages are active or not when students read words in Portuguese. To this end, the experiment proposed by Ormel et al. (2012) was replicated for bilingual children from the Dutch Sign Language pair and Dutch, with bilingual deaf students from the Libras-Portuguese pair, aged between ten and twenty-two years old, enrolled from the 5th year of Elementary School onwards. The task consisted of presenting image-word pairs in Portuguese, in which participants needed to determine whether the image and the word corresponded to the same concept. Among the selected image-word pairs, there are (i) conceptually unrelated pairs whose underlying signs in Libras share phonological parameters (they are phonologically similar) and pairs whose underlying signs have no phonological similarity; and (ii) related word-picture pairs in which the underlying signal is strongly iconic and pairs in which the underlying signal is not strongly iconic. To select the stimuli for the experiment, two previous studies were carried out: (i) a task judging the phonological similarity of signs, in which deaf and hearing Libras signers participated and judged the similarity of pairs of signs; (ii) an iconicity judgment task, in which hearing children with no knowledge of Libras participated who needed to “discover” the meaning of some signs. The research analyzed the participants' reaction time to detect facilitation and inhibition effects related to the phonological similarity and iconicity of the signs. Considering reaction time and patterns of successes and errors, the research results revealed no significant differences in experimental conditions, nor consistent facilitation or inhibition effects resulting from bimodal linguistic coactivation. The discussion of the results critically analyzes factors such as the complexity arising from aspects linked to different profiles of deaf people and other factors that may have influenced the research. Although the results did not corroborate the initial hypotheses, they contribute to the discussion about the complexity of bimodal coactivation, paving the way for new investigations on the topic.